Geology, geochemistry and mineralogy of the tareek darreh gold deposit, north of torbat-e jaam, northeast iran (2010)
The Tareek Darreh gold deposit is located 40km north of Torbat-e Jaam in the Khorasan-Razavi province, NE-Iran. The study area is mainly comprised of slightly metamorphosed, sedimentary rocks of Jurassic age including alternation of shale, siltstone, and sandstone. These rocks have been intruded by plutonic rocks such as gabbronorite, diorite, quartz-diorite, and rhyodacite. The ore bodies were exposed after trenching and pitting. In this study, all trenches and pits were systematically sampled and analysed by XRF, XRD, and ICP methods as well as petrological mineralogical studies. The alteration minerals of quartz, chlorite, albite, and sericite are mostly observed on the top or margin of the stocks. Alteration is more intensive at the contacts of the stocks where vein type mineralization has occurred. The veins are mainly composed of quartz and calcite  with arsenopyrite, chalcopyrite, and pyrite main ore minerals. Four promising mineralization zones were selected for further studies. The analytical results for the zones No. 2 and No. 4 confirm high gold, copper, bismuth, tellurium, and silver. In the zone No. 2 (50 x 80 m2) an average of 3.5ppm gold was recorded for one of the trenches, while in zone No. 4 (50 x 250m2). The average gold content is 1.35ppm. According to our studies, The Tareek Darreh gold deposit is considered to be similar to the "intrusion-related gold systems".